Cardiac magnetic resonance T1 mapping. Part 2: Diagnostic potential and applications. Issue 109 (December 2018) - Reiter, Ursula; Reiter, Clemens; Kräuter, Corina; Fuchsjäger, Michael; Reiter, Gert
Graphical abstract: Highlights: Associations of myocardial T1 and ECV with biopsy parameters differ by pathology. Disease-related T1 and ECV z-scores overlap. T1 mapping improves the diagnosis of myocarditis, iron overload and amyloidosis. T1 mapping enables non-contrast evaluation of AFD, PH and athlete's heart. T1 metrics for cardiac masses need to be introduced. Abstract: Non-invasive identification and differentiation of myocardial diseases represents the primary objectives of cardiac magnetic resonance (CMR) longitudinal relaxation time (T1) and extracellular volume (ECV) mapping. Given the fact that myocardial T1 and ECV values overlap throughout and within left ventricular phenotypes, a central issue to be addressed is whether and to what extent myocardial T1 and ECV mapping provides additional or superior diagnostic information to standard CMR imaging, and whether native T1 mapping could be employed as a non-contrast alternative to late gadolinium enhancement (LE) imaging. The present review aims to summarize physiological and pathophysiological alterations in native T1 and ECV values and summarized myocardial T1 and ECV alterations associated with cardiac diseases to support the translation of research findings into routine CMR imaging.